Ecological distribution of the hermit crab Dardanus insignis in shallow waters of the tropical-subtropical transition zone on the Brazilian coast - Frameschi, Israel F. [UNESP]; Andrade, Luciana S. [UNESP]; Fransozo, Vivian [UNESP]; Fernandes-Góes, Lissandra C. [UNESP]; Furlan, Michele [UNESP]; Fransozo, Adilson [UNESP] (Springer Nature, 2016)
Dardanus insignis is the most abundant hermit crab on sublittoral of soft bottoms along the southeastern coast of Brazil. It is among the Decapoda species that structure the macrobenthic community, from shallow regions to deeper areas up to 100 m. This study evaluated the distribution of D. insignis in a tropical-subtropical transition zone. In three bays (Ubatumirim, Ubatuba and Mar Virado), sampling was conducted monthly for two years, on four transects parallel to the coastline (at depths of 5, 10, 15, and 20 m), as well as one transect sheltered from wave action, and another in a more exposed area. Environmental variables were monitored in each sampling. The size fractions of coarse, medium and fine sand showed a positive correlation with the distribution of demographic groups on transects 15 and 20 m deep. On the other hand, the mean grain size (Phi) and silt+clay are negatively correlated with the distribution of the species. Adult males and females showed no environmental-specific relationship similar to the juveniles, and ovigerous females were negatively correlated by the bottom temperature. These results reveal that D. insignis is found in greater abundance on transects farther from the coastline, places that are less affected by the continual environmental oscillations in coastal regions and which, therefore, offer greater protection and stability for hermit crabs.
Keywords: Diogenidae; Distribution; Environmental factors; Spatial variation